Dog ownership, the natural outdoor environment and health: a cross-sectional study. Issue 5 (27th May 2019) - Zijlema, Wilma L; Christian, Hayley; Triguero-Mas, Margarita; Cirach, Marta; van den Berg, Magdalena; Maas, Jolanda; Gidlow, Christopher J; Kruize, Hanneke; Wendel-Vos, Wanda; Andrušaitytė, Sandra; Grazuleviciene, Regina; Litt, Jill; et al.
Abstract : Objectives: Dog owners walking their dog in natural outdoor environments (NOE) may benefit from the physical activity facilitated by dog walking and from time spent in nature. However, it is unclear whether dog owners receive additional health benefits associated with having access to NOE above the physical activity benefit of walking with their dog. We investigated associations between dog ownership, walking, time spent in NOE and health and whether these associations differed among those with good and poor access to NOE and those living in green and less green areas. Design: Cross-sectional study. Setting: The Positive Health Effects of the Natural Outdoor Environment in Typical Populations in Different Regions in Europe project. Participants: n=3586 adults from Barcelona (Spain), Doetinchem (the Netherlands), Kaunas (Lithuania) and Stoke-on-Trent (UK). Data collection and analysis: We calculated access to NOE with land maps and residential surrounding greenness with satellite data. Leisure time walking, time spent in NOE and general and mental health status were measured using validated questionnaires. Associations were estimated using multilevel analysis with a random intercept defined at the neighbourhood level. Results: Dog ownership was associated with higher rates of leisure time walking and time spending in NOE (OR 2.17, 95% CI 1.86 to 2.54 and 2.37, 95% CI 2.02 to 2.79, respectively). These associations were stronger in those living within 300 m of a NOE and in greener areas. No consistent associations were found between dog ownership and perceived general or mental health status. Conclusions: Compared with non-dog owners, dog owners walked more and spent more time in NOE, especially those living within 300 m of a NOE and in greener areas. The health implications of these relationships should be further investigated. In a largely physically inactive society, dog walking in NOE may be a simple way of promoting physical activity and health.